COMPARISON OF SERIAL AND APPROXIMATE ENTROPY TEST STATISTICS - N. G. Kiyevets; A. I. Korzun (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
It is shown that mathematical expressions for serial and approximate test statistics are equivalent on conditions that concerned overlapping series have the same lengths and observable sequence length →∞. The test result coincidence is experimentally confirmed.